Ooidonk 78 : Belgische Kunst, 1969 - 1977. (Bachte-Maria-Leerne : Kulturele kring van Bachte-Maria-Leerne, 1978)
De Clerck, Antoon ; Wittevrongel, Roger ; Raveel, Roger ; van Snick, Philippe ; De Smet, Yves ; Mees, Guy ; Charlier, Jacques ; Broodthaers, Marcel ; Dubosq, Jean ; Vercruysse, Jan ; etc.
Ooidonk 78 : Belgische Kunst, 1969 - 1977, Kasteel van Ooidonk, Bachte-Maria-Leerne, 1978
boek
Keywords: België